Involvement of the STING signaling in COVID-19 - Xiao, Ruoxuan; Zhang, Ao (Frontiers in Immunology, 2022)
The coronavirus disease 2019 (COVID-19) pandemic caused by the infection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has cast a notorious damage to the public health and global economy. The Stimulator of Interferon Genes (STING) is a crucial element of the host antiviral pathway and plays a pivotal but complex role in the infection and development of COVID-19. Herein, we discussed the antagonistic mechanism of viral proteins to the STING pathway as well as its activation induced by host cells. Specifically, we highlighted that the persistent activation of STING by SARS-CoV-2 led to abnormal inflammation, and STING inhibitors could reduce the excessive inflammation. In addition, we also emphasized that STING agonists possessed antiviral potency against diverse coronavirus and showed adjuvant efficacy in SARS-CoV-2 vaccines by inducing IFN responses.